Pencegahan Pernikahan Dini: Strategi Membangun Kesadaran Hukum untuk Mewujudkan Masa Depan Lebih Baik: Early Marriage Prevention: Strategy to Build Legal Awareness to Create a Better Future - Tahir, Muhammad; Djun’astuti, Erni; Agus, Agus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Marriage at an early age is a phenomenon that is still happening in the Long Sand Village, the Eastern Mempawah district, the district of Mempawha, and areas with low educational and economic levels. Early marriages have a wide range of negative effects, both in terms of health, psychology, and society. Lack of legal understanding of the age limit for marriage and its legal consequences are often the main cause. Therefore, increased legal awareness in society has become crucial to reducing the number of early marriages. This dedication is aimed at raising public awareness and understanding of the law relating to marriage at an early age, as well as providing education on the negative impact of early marriage and the importance of postponing marriage to a more mature age. The dedication takes place through several stages, namely an initial survey to measure the level of public understanding, socialization, and education through workshops, and targeted group discussions. In addition, legal support services and advice are provided for families vulnerable to early marriage. The activity has been successful in raising awareness and understanding of the law amongst the public, especially regarding the age limit for marriage and the negative impact of early marriage. The active participation of adolescents and parents in the discussion indicates a change in attitude and increased commitment to postponing early marriages. Evaluations through post-activity questionnaires show a significant improvement in legal understanding and awareness of the importance of education and self-development for adolescents.